Writing about everyday beauty in a northern village:an argument for diversity of habitable places - Rautio, P. (Pauliina) (University of Oulu, 2010)
Abstract The two rhetorical approaches to Finnish Lapland are the mythical and the miserable produced in the realms of tourism and politics respectively. The locals comply with neither. In this research the notion of beauty is used in seeking to understand how life is perceived as good-enough by particular villagers of a remote northern village. The scope of this research is novel theoretically and methodologically. The combination of everyday life aesthetics and education outside of institutional art education is rare and the method of data collection, collective correspondence, is created for the purposes of this research. Education is approached in this research as our perpetual growing in everyday life. Education and aesthetics receive support from sociology and human geography as well as environmental ethics. The theoretical frame leans on Ludwig Wittgenstein’s notions of language use: language is woven into the actions of ordinary life, used not only to describe but to act on and transform the world. The objectives of this research in brief are to 1) complement art-centered definitions of the notion of beauty, 2) argue for the significance of diversity of habitable places, and 3) to contribute positively to the prevailingly negative research rhetoric on life in northern Finnish villages. These objectives are tackled with research tasks unfolding as descriptive, interpretative and methodological respectively: 1) of what kind is perceived beauty in everyday life led in a small northern village? 2) What is the significance of considering beauty in everyday life? 3) What kind of data does correspondence yield on perceived beauty? There are four women participating in this research. They exchanged letters on the topic of everyday beauty once a month for a year. Together they comprise a group that varies in ages, education, employment, family structures and the length of stay in the village. What they share is a view of their home village as a good-enough place to live in. The main data consists of 44 letters ...